Analisis Kerja Sama Antara Guru Orang Tua dan Siswa dalam Mengatasi Gejala Kesulitan Belajar Tematik Bermuatan PPKN Saat BDR (Belajar Dari Rumah) di Kelas IV SDN 8 Bengkulu Tengah - Fitri Yunita; Puspa Djuwita; Abdul Muktadir (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
This study aims to describe the analysis of cooperation between teachers, parents and students in thematic learning difficulties charged with PPKN during BDR (learning from home) in grade IV SDN 8 Bengkulu Tengah. This type of research is qualitative with a descriptive study method. The subjects of the study were teachers, parents and students. Research instruments using observation guidelines, interviews and documentation. Data were analyzed through data collection, data reduction, data display, conclusion drawing/verification. The implementation of the learning is not optimal but has been passionate about the expected BDR learning.